Moral orientations as a factor of family self-determination development of modern students - S. V. Merzlyakova (Obrazovanie i Nauka)
Introduction. The phenomena of the family-demographic crisis in modern society make it necessary to study socio-psychological factors determining the actualisation and development of family self-determination of young people in the context of digital socialisation. Within the framework of digital socialisation, an open and contradictory information space determines the nature of marriage and family ideas, which are the indicative basis for the implementation of family behaviour by young men and women.Aim. The aim of the research is to identify the features of family self-determination of Russian students, who have different moral orientations and personality types in adolescence and early adulthood.Methodology and research methods. The theoretical and methodological basis of the study consists of: cultural-historical theory of psychological development and the doctrine of a psychological age by L. S. Vygotsky; age and psychological approach to the analysis of mental development in ontogenesis; theories of family self-determination of the individual; the concept of personality orientation by B. S. Bratus; concepts of moral self-determination by A. B. Kupreichenko, A. E. Vorobieva, Q. Guo, P. Sun, M. Cai, X. Zhang, K. Song; theories of prosocial behaviour by K. R. Bell, C. J. Showers; L. Kamas, A. Preston. The study involved 490 students, mostly enrolled in the humanities educational programmes. To achieve the goal, the author applied theoretical and methodological analysis of scientific literature; methods of comparison, generalisation, concretisation; psychodiagnostic method and mathematical and statistical methods of data processing.Results. The conducted research has shown that the dominant moral orientation of the personality in adolescence and early adulthood is a peace-building orientation. As a result of comparative analysis of the structural and content characteristics of family self-determination depending on personal moral orientation at different stages of age development, general and specific features were identified. The invariant characteristic is manifested in the fact that in the humanistic orientation there is a high importance of the value of happy family life; in the peace-building orientation – the strength of roles claims in the sphere of social activity for the stability of marriage and family relations, the importance of such marriage motives as self-actualisation and security; the probability of marriage regulated by unproductive feelings of revenge increases in the egocentric orientation. Adolescence is a sensitive period to form a cognitive component of family self-determination of student youth through the development of spiritual and moral sphere. The period of early adulthood is the most sensitive for the development of value-emotional and regulatory-behavioural component of family self-determination as a result of purposeful education of humanistic and peace-building orientation of students’ personality.Scientific novelty of the research lies in the establishment of the connection between the moral orientation of the personality and meaningful characteristics of family self-determination of students in adolescence (17–19 years) and early adulthood (20–22 years).Practical significance. The research materials and findings can be used for creating the education programmes in the organisations of higher education and for planning measures to preserve and develop traditional family values in the youth environment.